Inhibitory Control, Task/Rule Switching, and Cognitive Planning in Vascular Dementia: Are There Any Differences From Vascular Aging? - Pantsiou, Krystallia; Sfakianaki, Ourania; Papaliagkas, Vasileios; Savvoulidou, Dimitra; Costa, Vassiliki; Papantoniou, Georgia; Moraitou, Despina (Frontiers in Aging Neuroscience, 2018)
Recent studies have shown that patients diagnosed with Vascular Dementia (VaD) exhibit deficits in executive functions. According to “vascular hypothesis of cognitive aging,” community-dwelling older adults having risk factors for vascular disease development (RVD) may suffer from cognitive decline of the same type. The aim of the study was to assess the level of specific executive functions (EF) that have been revealed as most affected by vascular abnormalities, in older adults with incipient VaD and RVD. Subsequently specific ways of EF measuring could be suggested for more accurate diagnosis of early stage VaD. The study compared three adult groups (N = 60): (a) patients diagnosed with incipient VaD, according to DSM-5 criteria (n = 20); (b) community-dwelling older adults presenting cardiovascular risk factors (RVD; n = 20); (c) healthy young adult controls (n = 20). Three types of executive functions were examined: inhibitory control, cognitive flexibility as rule/task switching, and planning. The following D-KEFS subtests were administered for their evaluation: The ‘Color-Word Interference Test,’ the ‘Verbal Fluency Test,’ and the ‘Tower Test.’ Mixed-measures ANOVA, MANOVA, and one-way ANOVA as well as Scheffe post hoc test were applied to the data of the scores in each condition of each test. The results showed that VaD patients had significantly lower performance in test conditions requiring switching and planning, compared to RVD group and young controls. The specific deficits of VaD patients, compared to older adults presenting RVD according to multiple-group path analyses were: more uncorrected errors in inhibition, the use of semantic knowledge primarily instead of switching ability to switch between semantic categories, as well as a lower level of movement precision in planning.